Uniminuto and his social commitment to childhood - Luz Esperanza Bustos Sierra; Zaily del Pilar García Gutiérrez (Corporación Universitaria Minuto de Dios, 2009)
This article briefly describes some of the conceptualizations of childhood education that have been evolving along time and that have contributed to an understanding of children as rights holders, leading to the emergence of different social, political, and academic movements, which make their determination evident in the creation of national and international organizations to guarantee the children's well-being. UNIMINUTO responds to its social commitment with the creation of the undergraduate program in childhood pedagogy as an alternative of vocational training that will make the existence of society possible.